2016
DOI: 10.1038/ncomms11223
|View full text |Cite
|
Sign up to set email alerts
|

Capillarity ion concentration polarization as spontaneous desalting mechanism

Abstract: To overcome a world-wide water shortage problem, numerous desalination methods have been developed with state-of-the-art power efficiency. Here we propose a spontaneous desalting mechanism referred to as the capillarity ion concentration polarization. An ion-depletion zone is spontaneously formed near a nanoporous material by the permselective ion transportation driven by the capillarity of the material, in contrast to electrokinetic ion concentration polarization which achieves the same ion-depletion zone by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Therefore, the width of hydrogel was almost unchanged at pH = 3.5, while it expanded by 23% after 1 h in the solution of pH = 5.5 as shown in Figure 6a. When the swollen hydrogel blocked a microchannel, the configuration of microchannel was changed into micro-nano-micro-connection because the hydrogel possesses a number of nanopores inside [26,29,51]. Consequently, one can expect ICP phenomenon with the swollen hydrogel.…”
Section: Nanofluidic Sensing Of Ph Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the width of hydrogel was almost unchanged at pH = 3.5, while it expanded by 23% after 1 h in the solution of pH = 5.5 as shown in Figure 6a. When the swollen hydrogel blocked a microchannel, the configuration of microchannel was changed into micro-nano-micro-connection because the hydrogel possesses a number of nanopores inside [26,29,51]. Consequently, one can expect ICP phenomenon with the swollen hydrogel.…”
Section: Nanofluidic Sensing Of Ph Stimulationmentioning
confidence: 99%
“…Since the ion depletion zone in ICP acts as an electrical filter together with zero-Reynolds number characteristics, it has been actively utilized for low abundance biomolecular separation / accumulation device [21][22][23]. If one can extract the solution from the ion depletion zone, one can use it as portable scale electro-desalination / purification [1,[24][25][26][27] device. However, shared fundamental aspects of ICP and CP have been actively studied such as vortex generation [9][10][11]28], stabilization [17,[29][30][31], mechanism of overlimiting current [12][13][14]16,18,20], phenomenon near nanopores [32][33][34][35] and concentration profile including pH variation [36][37][38], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work presented the spontaneous preconcentration (or selective preconcentration) method in microfluidic chip with leveraging convective flow through microchannel over diffusiophoresis induced by imbibition and ion exchange of ion exchange medium, respectively [13][14][15][16][17][18]. Especially, we had demonstrated that the velocity of the convective flow by the imbibition of the medium deviated from original Darcy's law using non-uniformly patterned ion exchange medium, but this work has the limitation of time-consuming and complex process [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is still a challenge to prepare high efficiency, reusable and broad-spectrum adsorbents. Recently, polymeric hydrogels have been considered as high performance materials for environmental applications such as desalination 30 , heavy metal ions removal 31 and radionuclides 32 due to their advantageous characteristics including adsorption-regeneration ability, economic feasibility, and environmental compatibility. However, there are few of studies on the removal of dyes using polymeric hydrogels.…”
Section: Introductionmentioning
confidence: 99%